The identity of Cintractia disciformis: reclassification and synonymy of a southern Asian smut parasitic on Carex sect. Aulocystis - M. Piątek (IMA Fungus)
The identity of a neglected smut fungus, Cintractia disciformis, described from Carex hirtella in the Western Himalaya, India is reassessed. The species is excluded from Cintractia and is confirmed as a distinct species of Anthracoidea. Two smuts, A. nepalensis on Carex nakaoana in Nepal, and A. haematostomae on Carex haematostoma in China, are similar morphologically and considered to be later heterotypic synonyms of Cintractia disciformis. The appropriate nomenclatural combination for this species, Anthracoidea disciformis comb. nov., is validated.